Hexosamine biosynthesis and related pathways, protein N-glycosylation and O-GlcNAcylation: their interconnection and role in plants - Chen, Ya-Huei; Cheng, Wan-Hsing (Frontiers in Plant Science, 2024)
N-Acetylglucosamine (GlcNAc), a fundamental amino sugar moiety, is essential for protein glycosylation, glycolipid, GPI-anchor protein, and cell wall components. Uridine diphosphate-GlcNAc (UDP-GlcNAc), an active form of GlcNAc, is synthesized through the hexosamine biosynthesis pathway (HBP). Although HBP is highly conserved across organisms, the enzymes involved perform subtly distinct functions among microbes, mammals, and plants. A complete block of HBP normally causes lethality in any life form, reflecting the pivotal role of HBP in the normal growth and development of organisms. Although HBP is mainly composed of four biochemical reactions, HBP is exquisitely regulated to maintain the homeostasis of UDP-GlcNAc content. As HBP utilizes substrates including fructose-6-P, glutamine, acetyl-CoA, and UTP, endogenous nutrient/energy metabolites may be integrated to better suit internal growth and development, and external environmental stimuli. Although the genes encoding HBP enzymes are well characterized in microbes and mammals, they were less understood in higher plants in the past. As the HBP-related genes/enzymes have largely been characterized in higher plants in recent years, in this review we update the latest advances in the functions of the HBPrelated genes in higher plants. In addition, HBP's salvage pathway and GlcNAc-mediated two major co-or post-translational modifications, N-glycosylation and O-GlcNAcylation, are also included in this review. Further knowledge on the function of HBP and its product conjugates, and the mechanisms underlying their response to deleterious environments might provide an alternative strategy for agricultural biofortification in the future.